Site-Specific Nutrient Management: Implementation guidance for policymakers and investors - Richards, Meryl B.; Butterbach-Bahl, Klaus; Jat, Mangi Lal; Ortíz Monasterio, Jose Iván; Sapkota, Tek Bahadur; Lipinski B (2015)
Site-Specific Nutrient Management (SSNM) provides guidance relevant to the context of farmers' fields. SSNM maintains or enhances crop yields, while providing savings for farmers through more efficient fertilizer use. By minimizing fertilizer overuse, greenhouse gas emissions can be reduced, in some cases up to 50%. SSNM optimizes the supply of soil nutrients over space and time to match crop requirements. SSNM increases crop productivity and improves efficiency of fertilizer use. SSNM mitigates greenhouse gases from agriculture in areas with high nitrogen fertilizer use. Incentives for adoption of SSNM depend strongly on fertilizer prices.